2012
DOI: 10.1111/j.1365-3121.2012.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Sheath fold formation around slip surfaces

Abstract: Terra Nova, 24, 417–421, 2012 Abstract Sheath folds are associated with shear zones and have been used as high strain indicators. We present results from a three‐dimensional analytical study showing that the flow perturbation around a planar weakness acting as a slip surface, in simple shear leads to the formation of sheath folds at low shear strain. Closed traces of marker layers are exhibited in cross‐sections cut perpendicular to the shear direction in the vicinity of the slip surface tip. In cross‐sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Reber et al. () showed that closed contours with R yz <3 are difficult to generate in simple‐shear deformation, even if the initial orientation and aspect ratio of the slip surface are varied. Alsop and Holdsworth () suggested that R yz <3 is generally obtained in constrictional deformation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reber et al. () showed that closed contours with R yz <3 are difficult to generate in simple‐shear deformation, even if the initial orientation and aspect ratio of the slip surface are varied. Alsop and Holdsworth () suggested that R yz <3 is generally obtained in constrictional deformation.…”
Section: Discussionmentioning
confidence: 99%
“…We study a three‐dimensional mechanical model of sheath fold formation around a pre‐existing, initially circular slip surface embedded in a homogeneous, isotropic, linear viscous matrix (Exner & Dabrowski, ; Reber et al., ). We obtain the velocity field using the external Eshelby solution (Eshelby, ), which is modified for the case of an incompressible viscous matrix and an elliptical and inviscid inclusion.…”
Section: Mechanical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…(Reber et al, 2013). (C) Cross section from an analytical model investigating the effect of total shear strain (Reber et al, 2012). experimental community requires coordinated and structured growth in the numbers of researchers involved in physical experiments as well as instructors engaging students with classroom experiments.…”
Section: The Revolution In Physical Experimentsmentioning
confidence: 99%